2021
DOI: 10.3102/00028312211060855
|View full text |Cite
|
Sign up to set email alerts
|

Improving Low-Performing Schools: A Meta-Analysis of Impact Evaluation Studies

Abstract: The public narrative surrounding efforts to improve low-performing K–12 schools in the United States has been notably gloomy. But what is known empirically about whether school improvement works, which policies are most effective, which contexts respond best to intervention, and how long it takes? We meta-analyze 141 estimates from 67 studies of post–No Child Left Behind Act turnaround policies. On average, policies had moderate positive effects on math and no effect on English Language Arts achievement on hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 94 publications
0
27
0
Order By: Relevance
“…Interestingly, in a meta‐analysis of studies of reforms designed to improve low‐performing schools, Schueler et al. (2020) also find that the benefits from these reforms have been concentrated in majority Hispanic contexts. Regardless of the mechanisms, these two studies together suggest that takeover is particularly risky for both the adults and children in majority‐African American communities.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a meta‐analysis of studies of reforms designed to improve low‐performing schools, Schueler et al. (2020) also find that the benefits from these reforms have been concentrated in majority Hispanic contexts. Regardless of the mechanisms, these two studies together suggest that takeover is particularly risky for both the adults and children in majority‐African American communities.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests there is no significant evidence that turnaround efforts help states meet academic outcomes (Redding & Nguyen, 2020). The utility of these changes is better evidenced the longer the interventions are in place (Schueler et al, 2020). The wide range of potential approaches and outcomes within turnaround policies muddy the waters regarding their effectiveness and how they diffuse.…”
Section: Turnaround Policymentioning
confidence: 99%
“…State policies to intervene in education, including turnaround and takeover, have proliferated throughout the past 40 years with differing degrees of effectiveness (Oluwole & Green, 2009; Redding & Nguyen, 2020; Schueler et al, 2020; Welsh et al, 2017; Welsh & Williams, 2018). Takeover policies are based on intervention through direct action such as taking over school boards or schools (Bross et al, 2016; Jochim & Pillow, 2019).…”
mentioning
confidence: 99%
“…The theory of change behind this model is a disruption of the status quo, often including a restructuring of school governance and management, a renewed focus on talent management, and improvements to school climate (Redding & Nguyen, 2020;Zimmer et al, 2017). Specific turnaround strategies have included strengthening teacher effectiveness, curriculum changes, expanded learning time, and flexibility and support for school operators (Kutash et al, 2010;Schueler et al, 2020). Another common turnaround strategy is for the state or local education agency to replace the current school principal (Hurlburt et al, 2012;Kutash et al, 2010;Zimmer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On average, school turnaround has shown little evidence of producing sustained school improvement (Dragoset et al, 2016(Dragoset et al, , 2017Pham et al, 2020). Furthermore, research finds that different approaches to school turnaround vary in their effectiveness (Redding & Nguyen, 2020;Schueler et al, 2020). For example, one set of studies found that a turnaround model maintaining local governance with increased autonomy outperformed a state takeover model in which school management was largely turned over to charter management organizations (CMOs) (Henry et al, 2020.…”
Section: Introductionmentioning
confidence: 99%